Dissociating Orienting Biases From Integration Effects With Eye Movements. (March 2018) - Hilchey, Matthew D.; Rajsic, Jason; Huffman, Greg; Klein, Raymond M.; Pratt, Jay
Despite decades of research, the conditions under which shifts of attention to prior target locations are facilitated or inhibited remain unknown. This ambiguity is a product of the popular feature discrimination task, in which attentional bias is commonly inferred from the efficiency by which a stimulus feature is discriminated after its location has been repeated or changed. Problematically, these tasks lead to integration effects; effects of target-location repetition appear to depend entirely on whether the target feature or response also repeats, allowing for several possible inferences about orienting bias. To parcel out integration effects and orienting biases, we designed the present experiments to require localized eye movements and manual discrimination responses to serially presented targets with randomly repeating locations. Eye movements revealed consistent biases away from prior target locations. Manual discrimination responses revealed integration effects. These data collectively revealed inhibited reorienting and integration effects, which resolve the ambiguity and reconcile episodic integration and attentional orienting accounts.